Optimization of Vacuum Forming Parameter Settings to Minimize Burning Defect on Strawberry Packaging Products Using the Taguchi Method - Th. Adi Nugroho; Adhi Setya Hutama; Perwita Kurniawan (Universitas Sanata Dharma, 2022)
Packaging products are being developed by PT. ATMI IGI – Center. The process of making these products uses the Vacuum forming method. The packaging product is made of PP (Polypropylene) and is used to pack strawberries. There are several problems during the production process, one of which is that there are still product defects burning or often called burn marks. These problems are caused by the machining parameters that have not been standardized, and based on trial eror or experience of the operator. The vacuum forming machine used in this production is the Formech 508FS Vacuum Forming machine. The optimized parameters are heat zone, heat time, and stand by temperature. Optimizing these parameters using the Taguchi method, with an orthogonal array with 9 trials, and the selected signal to noise ratio (SNR) is smaller is better. The response of this research is the reduction of burn mark product defects. The results showed that to reduce burn mark product defects, is to set the parameter heat zone 1 by 90%, heating zone 2 is 80%, heating time 45s, and stand by temperature 60%. Based on this arrangement, the product defects obtained only reached 13%. PT. ATMI IGI-Center is expected to be able to use these parameter settings for the strawberry packaging production process.